A multi-element doped sodium ion battery manganese-based layered oxide positive electrode material and its preparation method and application
By using a multi-doped sodium ion battery manganese-based layered oxide cathode material in the P2 cathode material, the synergistic action of Zr and Sn is used to solve the problem of multi-platform and high-voltage phase change during the charge and discharge process of P2 cathode material, and the structural stability and electrochemical performance of the material are improved.
Patent Information
- Application Number
- CN202411922676.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
There are multi-platform and high-voltage phase transition problems in the charging and discharging process of P2 type positive electrode materials, which affects its cycle stability and rate performance.
Using a multi-doped manganese-based layered oxide positive electrode material of sodium ion battery, the chemical formula is Na0.67Ni0.33MnaMbO2, the structural stability of the material and the stability of the sodium ion diffusion channel are enhanced by doping transition metal elements such as Cu, Sn, Zr or Ti, especially Zr and Sn.
It effectively suppresses the adverse phase change of the positive electrode material under high pressure, improves the structural stability and electrochemical properties of the material, and shows excellent rate performance and cycle life.
Smart Images

Figure CN119764435A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a layered oxide, and in particular to a multi-doped manganese-based layered oxide positive electrode material for a sodium ion battery, and a preparation method and application thereof. Background Art
[0002] Positive electrode materials play a vital role in the entire battery system. With the rise and development of new energy technologies, sodium-ion batteries have a similar working principle to lithium-ion batteries due to their high abundance and similar physical and chemical properties to lithium: during the charge and discharge process, sodium ions are intercalated and deintercalated between the positive electrode, diaphragm, and negative electrode, and electrons are transmitted in the external circuit to achieve the conversion of chemical energy to electrical energy. In addition, sodium-ion batteries and lithium-ion batteries have similar production line processes, so they have broad development prospects. Among the many positive electrode materials for sodium-ion batteries, layered transition metal oxides have advantages such as high theoretical specific capacity and simple synthesis process. According to the occupancy of sodium and the stacking order of oxygen, layered transition metal oxides can be divided into four phase structures: P2, O2, P3 and O3. Among them, P2 and O3 crystal phases have been widely studied by researchers because of their relatively stable configurations. Compared with O3-type oxide positive electrodes, P2-type positive electrode materials have broader sodium diffusion channels and better structural stability, and multiple element doping can promote lattice stability. However, due to the diversity of doping elements, it is still challenging to balance lattice stability, battery charge and discharge specific capacity and cycle stability to obtain the ideal high-performance cathode material. At present, P2-type cathode materials mainly face problems such as multiple platforms and high-voltage phase transitions during the charge and discharge process, which affect their cycle stability and rate performance. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to improve the problems of multi-platform and high-voltage phase transitions in the charging and discharging process of the positive electrode material, and to provide a multi-doped manganese-based layered oxide positive electrode material for a sodium ion battery; another purpose of the present invention is to provide a method for preparing the oxide positive electrode material; another purpose of the present invention is to provide the application of the oxide positive electrode material in the positive electrode material of a sodium ion battery.
[0004] Technical solution: The multi-doped sodium ion battery manganese-based layered oxide positive electrode material of the present invention has a chemical formula of Na 0.67 Ni 0.33 Mn a M b O2, wherein 0.25≤a≤0.67, 0≤b≤0.4, and M is a transition metal element.
[0005] Furthermore, the transition metal M comprises one or more of Cu, Sn, Zr or Ti, preferably Zr and Sn. The transition metal-O bonding ability is strong, and the Zr-O bond energy is greater than the Mn-O bond energy, which shortens the spacing of the TM layer and expands the spacing of the Na layer, which is conducive to better storage of sodium. Sn doping makes the MO6 octahedral structure more stable, which is caused by the change in the TM-O bond length, making the material structure more stable and providing a more stable diffusion channel for sodium.
[0006] The present invention also provides a method for preparing the multi-element doped sodium ion battery manganese-based layered oxide positive electrode material, comprising the following steps:
[0007] (1) weighing sodium carbonate, nickel oxide, manganese trioxide and a transition metal compound according to a stoichiometric ratio and grinding and mixing them uniformly;
[0008] (2) The target product is obtained after high-temperature solid-phase sintering and cooling.
[0009] Furthermore, in the step (1), the amount of sodium carbonate weighed is 3% to 8% in excess of its own weight, so as to compensate for the loss of Na source during the high-temperature solid-phase sintering process.
[0010] Furthermore, the source of the transition metal element in step (1) is a transition metal oxide, such as copper oxide, titanium dioxide, zirconium oxide, tin oxide, etc. The solid compound mixed in step (1) is dispersed with 3-5 ml of anhydrous ethanol, which is beneficial to uniform mixing of the components, and the lattice formed in the subsequent high-temperature solid-phase sintering process is more uniform and stable, and is not prone to phase change.
[0011] Furthermore, the high temperature solid phase sintering conditions in step (2) are: 60°C ± 10°C forced air drying for 0.5 to 1 hour, 900°C ± 100°C muffle furnace calcination for 10 to 15 hours; the heating rate of the muffle furnace is 3 to 5°C / min. Appropriate sintering temperature, time and heating rate ensure that the material has good crystallinity and lattice stability.
[0012] The multi-doped sodium ion battery manganese-based layered oxide positive electrode material of the present invention can be applied to sodium ion battery positive electrode materials.
[0013] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: 1. The synergistic effect of doping with different transition metal elements is utilized to support the stability of the copper alloy TMO6 plate, effectively suppressing the adverse phase change of the positive electrode material under high pressure, making the lattice more stable, and the assembled half-cell and full-cell exhibit excellent electrochemical properties and kinetic characteristics; 2. It has excellent rate performance, and the discharge capacity can still reach 75.7mAh / g at 30C, and exhibits excellent cycle life, with a capacity retention rate of 85.7% after 1000 cycles at 30C; 3. The full cell assembled with the hard carbon negative electrode has a high discharge specific capacity of 123.1mAh / g at 0.1C. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 SEM images of materials prepared in Examples 5 to 7, 9 and Comparative Example 1;
[0015] Figure 2 XRD patterns of materials prepared in Examples 6, 8 and 9 and Comparative Example 1;
[0016] Figure 3 This is the first cycle charge and discharge curve of the material prepared in Example 5;
[0017] Figure 4 This is the first cycle charge and discharge curve of the material prepared in Example 6;
[0018] Figure 5 This is the first cycle charge and discharge curve of the material prepared in Example 7;
[0019] Figure 6 This is the first cycle charge and discharge curve of the material prepared in Example 8;
[0020] Figure 7 This is the first cycle charge and discharge curve of the material prepared in Example 9;
[0021] Figure 8 This is a full battery charge and discharge curve diagram of the material prepared in Example 9;
[0022] Fig. 9 This is the first cycle charge and discharge curve of the material prepared in Example 10;
[0023] Fig.10 This is the first cycle charge and discharge curve of the material prepared in Comparative Example 1;
[0024] Fig.11 This is a cycle curve diagram of the materials prepared in Examples 8 to 10 and Comparative Example 1. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below in conjunction with the examples and drawings. The materials used in the examples are all commercially available.
[0026] The embodiment and comparative example provide a multi-doped sodium ion battery manganese-based layered oxide positive electrode material, the chemical formula of which is Na 0.67 Ni 0.33 Mn a M b O2, M is one or more of the transition metal elements Cu, Sn, Zr or Ti. The ratios and synthesis conditions of the elements in different embodiments and comparative examples are detailed in Table 1. The blanks are for undoped related elements.
[0027] Examples 1 to 4 conducted doping experiments with a single transition metal element, Examples 5 to 7 conducted experiments with doping amounts of two elements Sn and Zr, and Examples 8 to 10 conducted multi-element doping experiments based on Example 6.
[0028] The synthesis method of the above embodiment and comparative example comprises the following steps:
[0029] (1) weighing sodium carbonate, nickel oxide, manganese trioxide and a transition metal compound in a stoichiometric ratio, grinding and mixing them evenly, wherein the amount of sodium carbonate weighed is 3% to 8% in excess of its own weight, and the mixed solid compound is dispersed with 3 to 5 ml of anhydrous ethanol;
[0030] (2) The target product is obtained after high-temperature solid-phase sintering and cooling. The high-temperature solid-phase sintering conditions are: forced air drying at 60°C±10°C for 0.5-1h, calcination in a muffle furnace at 900°C±100°C for 10-15h, and a heating rate of the muffle furnace of 3-5°C / min.
[0031] Table 1 Element ratios and synthesis conditions of each embodiment and comparative example
[0032]
[0033] The morphology and structure of the materials synthesized in the above examples and comparative examples were characterized by SEM and XRD.
[0034] The materials synthesized in the above embodiments and comparative examples were coated on aluminum foil with super-P and PVDF in a ratio of 7:2:1, and a glass fiber separator was used. The electrolyte was sodium perchlorate, and button cells were assembled and tested on a blue power test system. The voltage window was 2-4.2V, 1C=170mAh / g. All test characterization results are detailed in Table 2.
[0035] The materials synthesized in Examples 8 to 10 and Comparative Example 1 were combined into half-cells, and the capacity retention rate after 1000 cycles at 30C was tested. The materials synthesized in Example 9 were combined with hard carbon into full-cells, and the discharge capacity was tested at a current density of 0.1C.
[0036] Table 2 Test results of charge and discharge performance of various embodiments and comparative examples
[0037]
[0038] Comparing Examples 1 to 4 with Comparative Example 1, the experimental results show a typical hexagonal flake morphology, the material is successfully synthesized, and the lattice structure is good. Compared with Comparative Example 1, during the synthesis process, the doped transition metal elements support the stability of the copper alloy TMO6 plate, the layered structure is obvious and stable, and the adverse phase change of the positive electrode material under high pressure is effectively suppressed. The lattice is more stable, and the charge and discharge performance of the synthesized positive electrode material is better than that of Comparative Example 1. Among them, Examples 1 to 2 are doped with Sn or Zr alone, and the hexagonal particle morphology of the synthesized material particles is more standardized, the crystal structure is more stable, and the charge and discharge performance of the material is more stable. Zr doping, Zr-O bond energy (760kJ / mol) is stronger than Mn-O bond energy (402kJ / mol), increases the sodium interlayer spacing, and contributes to faster sodium ion deintercalation, thereby improving its rate performance. Sn doping makes the MO6 octahedral structure more stable, which is caused by the change in TM-O bond length, making the material structure more stable, and providing a more stable diffusion channel for sodium.
[0039] Based on the test results of Examples 1 to 4, Examples 5 to 10 discuss the performance of double-doped and multi-doped synthetic materials. Figure 1 It can be seen from the SEM image that, compared with the material synthesized in comparative example 1 without being doped with transition metal elements, the hexagonal sheet structure of the material synthesized by doping transition metal elements is regular and uniform, and the layered structure is obvious. Figure 2 The XRD diagram shows that the synthesized layered positive electrode exhibits a good crystalline phase, corresponding to the traditional P2-type nickel-manganese-based material, belongs to the P63 / mmc space group, has hexagonal close packing, has good crystallinity, good stability and conductivity, and is not prone to phase change.
[0040] Comparative Examples 5 to 7 and Comparative Example 1, Figures 3 to 5 It shows that the multi-platform phenomenon of the first cycle charge and discharge curve is weakened, the synergistic effect of Sn and Zr supports the stability of the copper alloy TMO6 plate, effectively inhibits the adverse phase change of the positive electrode material under high pressure, the lattice is more stable, the phase change process of the material during the charge and discharge process is alleviated, and the structural stability of the material is effectively improved. The charge and discharge performance results of the synthetic material are shown in Table 2. The results show that when the doping amount of Sn and Zr is controlled to make a=b=0.03, the material synthesized in Example 6 shows a higher level of discharge capacity and better charge and discharge performance, with a higher discharge specific capacity at 0.1C and 1C, 156.88mAh / g at 0.1C, and a discharge specific capacity of 30C is equivalent to that of Examples 5 and 7, and the first cycle coulomb efficiency is slightly lower than that of Examples 5 and 7.
[0041] Comparative Examples 8 to 10 and Comparative Example 1, Fig.10 compared to Figure 6 ,7 and 9 show that the charge and discharge curves of the materials synthesized in Examples 8 to 10 are smoother, and the first-cycle coulomb efficiency of multi-element doping is significantly improved compared with single-element doping or double-element doping, indicating that the disorder of each element in the system increases after multiple element doping, which is beneficial to the single-phase solid solution reaction of the material; compared with single metal oxide materials, the synergistic effect between elements is enhanced, and the multi-element doped material has a higher electronic conductivity and a more stable crystal structure, which improves the stability of the lattice during the phase change process. The test results of the charge and discharge performance of the synthesized materials in each embodiment of Table 2 show that compared with Examples 5 to 7, although the first-cycle coulomb efficiency is significantly improved, the discharge specific capacity of 0.1C, 1C and 30C decreases, especially in Example 10. With the increase of the transition metal element doping amount, the discharge specific capacity of 0.1C, 1C and 30C decreases significantly. This is mainly because during the continuous sodium deintercalation process, the TMO6 plate slips, causing an irreversible phase change, resulting in the collapse of the crystal structure, resulting in poor rate performance of the material; however, Fig.11 It shows that the cycle life of the synthesized material is significantly improved after multi-element doping. The capacity retention rate of Example 9 after 1000 cycles at 30C is 85.73%. This is mainly because Zr, Sn and O have stronger bonding ability, which effectively stabilizes the crystal structure of the material. At the same time, the distance between sodium layers is increased, which achieves faster sodium insertion and extraction kinetics. In addition, Figure 8 As shown, the material synthesized in Example 9 is combined with hard carbon into a full battery. The discharge capacity is tested to reach 124.24 mAh / g at a current density of 0.1C, and the application prospect is good. This is mainly because the various metal elements in the material act synergistically, the disorder of the system is increased, and the adverse phase change of the material under high pressure is alleviated, which helps to improve the performance of the material.
Claims
1. A multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries, characterized in that: The chemical formula is Na 0.67 Ni 0.33 Mn a M b O2, wherein 0.25≤a≤0.67, 0≤b≤0.4, and M is a transition metal element.
2. The multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to claim 1, characterized in that: The M transition metal includes one or more of Cu, Sn, Zr or Ti.
3. The multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to claim 2, characterized in that: The M transition metals are Zr and Sn.
4. A method for preparing a multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to any one of claims 1 to 3, characterized in that: The steps include: (1) weighing sodium carbonate, nickel oxide, manganese trioxide and a transition metal compound according to a stoichiometric ratio and grinding and mixing them uniformly; (2) The target product is obtained after high-temperature solid-phase sintering and cooling.
5. The method for preparing the multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to claim 4, characterized in that: In the step (1), the amount of sodium carbonate weighed is 3% to 8% in excess of its own weight.
6. The method for preparing the multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to claim 4, characterized in that: The source of the transition metal element in step (1) is a transition metal oxide.
7. The method for preparing the multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to claim 4, characterized in that: The solid compound mixed in step (1) is dispersed with 3-5 ml of anhydrous ethanol.
8. The method for preparing a multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to claim 4, characterized in that: The high temperature solid phase sintering conditions of step (2) are: forced air drying at 60°C±10°C for 0.5-1h, and calcination in a muffle furnace at 900°C±100°C for 10-15h.
9. The method for preparing a multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to claim 8, characterized in that: The heating rate of the muffle furnace is 3-5°C / min.
10. Use of the multi-doped manganese-based layered oxide positive electrode material for sodium ion batteries according to any one of claims 1 to 9 in positive electrode materials for sodium ion batteries.